2017
DOI: 10.1177/1077695817711611
|View full text |Cite
|
Sign up to set email alerts
|

Latin American Investigative Journalism Education: Learning Practices, Learning Gaps

Abstract: This study seeks to examine the state of investigative journalism practices used in higher education in Latin America. Using a meta-theoretical framework called the Community of Practice (CoP), this study seeks to identify whether a particular learning practice exists in this region. Based on an online survey conducted on Latin American educators and students, several gaps exist between them on the techniques and resources used to learn about investigative journalism. The implications of these findings are dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…Recently, progress has even been made toward the identification of subtle patterns that determine biases in journalistic framing (Morstatter et al, 2018). As explained by Schmitz- Weiss et al (2017), technology has eliminated the barriers to journalistic activity, making it possible to study and analyze information generated by the news itself.…”
Section: Interest In Textual Datamentioning
confidence: 99%
“…Recently, progress has even been made toward the identification of subtle patterns that determine biases in journalistic framing (Morstatter et al, 2018). As explained by Schmitz- Weiss et al (2017), technology has eliminated the barriers to journalistic activity, making it possible to study and analyze information generated by the news itself.…”
Section: Interest In Textual Datamentioning
confidence: 99%
“…This education gap is not unusual to the region as literature has noted overall that the latest journalism skills and training are lacking in the university systems in Latin America where overall, the students are not meeting the demands of what is needed in the newsroom due to a lack of proper scaffolding in the classroom (Arroyave & Barrios, 2012; Cleary, 2003; Ferreira et al, 2000; Herscovitz, 2012; Schmitz Weiss et al, 2017). This study is intended to be the first step toward filling this research gap by examining specifically innovation perceptions among journalism students, educators, and journalists.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The strong presence of investigative reporting in journalism education is undeniable, however. In Latin America and the Caribbean, 6 in 10 journalism educators and students from 20 countries who participated in a survey reported that investigative journalism is included in the curriculum in journalism schools (Weiss et al 2017). In the Philippines, investigative journalism became a mandatory course in all journalism programs at the undergraduate level in 2010 (Commission on Higher Education 2010).…”
Section: From Newsroom To Academementioning
confidence: 99%